Optimasi Penjadwalan Produksi Menggunakan Metode Run Out Time: Studi Kasus: PT. XYZ - Mustasyar, Mufid Ifam; Purnama, Jaka (SURYA TEKNIKA, 2025)
Effective production scheduling is essential to improve operational efficiency in manufacturing companies. This study analyzes the application of the Run Out Time (ROT) method in multi-product production scheduling at PT XYZ, which faces the challenges of demand fluctuations and high setup times. ROT is used to determine production priorities based on the ratio between inventory and average demand. Data for six months were analyzed including historical demand, production capacity, and operational time. As a result, the ROT method successfully reduced setup time and idle time, increased machine utilization, and reduced operational costs by Rp 75,500,000. Return on Investment (ROI) reached 196.08% with a Payback Period of two months. These findings prove that the ROT method is effective in optimizing scheduling, meeting demand on time, and preventing overproduction and underproduction. The application of ROT contributes to increasing the efficiency and competitiveness of PT XYZ in the competitive manufacturing market.